2023
DOI: 10.3389/fmars.2023.1233249
|View full text |Cite
|
Sign up to set email alerts
|

Differential larval growth strategies and trophodynamics of larval Atlantic bluefin tuna (Thunnus thynnus) from two discrete spawning grounds

Estrella Malca,
José M. Quintanilla,
Trika Gerard
et al.

Abstract: Atlantic bluefin tuna (ABT), Thunnus thynnus, is a globally important fishery resource. This oceanic top predator undertakes long-distance migrations from its nutrient-rich feeding grounds in the north Atlantic to oligotrophic spawning grounds. Larvae are born mainly in the corresponding ecosystems of its two well-established spawning areas: the Gulf of Mexico (GoM) and the Mediterranean Sea (MED). Stable isotopes analyses (SIA) of δ15N and δ13C have proven useful for understanding marine food webs and have ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…Similar observations have been reported for larval Shortbelly Rockfish where larvae with a lower TP were heavier and grew faster [101]. The TP reflects how the energy is transferred from the base of the food web up to the larva [99,102], and its estimation can be influenced by food chain efficiency [103,104], which causes a wide range of TP estimates in the GOM [64].…”
Section: Trophic Behavior (Post-flexion Larvae)supporting
confidence: 75%
See 4 more Smart Citations
“…Similar observations have been reported for larval Shortbelly Rockfish where larvae with a lower TP were heavier and grew faster [101]. The TP reflects how the energy is transferred from the base of the food web up to the larva [99,102], and its estimation can be influenced by food chain efficiency [103,104], which causes a wide range of TP estimates in the GOM [64].…”
Section: Trophic Behavior (Post-flexion Larvae)supporting
confidence: 75%
“…δ 15 N levels are enriched with each trophic transfer, providing information about the TPs of consumers [50,99]. In previous studies, better larval growth was found to be associated with higher TPs [56,64,100], which was interpreted as reflecting greater trophic specialization. According to our results, however, larvae with better growth from GOM18 had lower TPs than GOM17 (Table A1).…”
Section: Trophic Behavior (Post-flexion Larvae)mentioning
confidence: 92%
See 3 more Smart Citations